(untitled) (Boca Raton, Fl., 2002)
"Engineering and food for the 21st century" presents important reviews and up-to-date discussions of major topics relating to engineering and food. The first part bigins with recent trends in food engineering and challenges for the future. It then presents important discussions of fundamental aspects of food engineering, including physical chemistry, mass transfer, food rheology, and food structure. Part 2 contains state-of-the-art presentations on thermal processing and packaging, minimal processing, emerging technologies, process control, biotechnology, and environmental factors associated with the processing of food.
Keywords: Food industry and trade